Large intraductal sialolith in Wharton's duct - Shallu Tyagi; Suresh Yadav; Prince Kumar; Poonam Preet Bhandari (Wolters Kluwer Medknow Publications, 2013)
Sialolithiasis is one of the most common disease of salivary glands and it has been estimated that it affects 12 in 1000 of the adult population. More than 80% occur in the sub mandibular gland or its duct, 6% in the parotid gland and 2% in the sublingual gland or minor salivary glands and are a common cause of acute and chronic infections. Clinically, they are round or ovoid, rough or smooth and of a yellowish color. They consist of mainly calcium phosphate with smaller amounts of carbonates in the form of hydroxyapatite, with smaller amounts of magnesium, potassium, and ammonia. Sub mandibular stones are 82% inorganic and 18% organic material whereas parotid stones are composed of 49% inorganic and 51% organic material. The organic material is composed of various carbohydrates and amino acids. Bacterial elements have not been identified at the core of a sialolith and this report describes the case of a patient who had an unusual large submandibular gland sialolith (calculus) completely obstructing the sub mandibular gland duct. Patients with sialolithiasis require definitive surgical treatment in most cases, which results in an excellent prognosis.